Drivers of Participation Elasticities across Europe: Gender or Earner Role within the Household? - Charlotte Bartels; Cortnie Shupe (Institute of Labor Economics (IZA), 2018)
We compute participation tax rates across the EU and find that work disincentives inherent in tax-benefit systems largely depend on household composition and the individual's earner role within the household. We then estimate participation elasticities using an IV Group estimator that enables us to investigate the responsiveness of individuals to work incentives. We contribute to the literature on heterogeneous elasticities by providing estimates for different socioeconomic groups by country, gender and earner role within the household. Our results show an average elasticity of 0.08 for men and of 0.14 for women as well as a high degree of heterogeneity across countries. The commonly cited difference in elasticities between men and women stems predominantly from the earner role of the individual within the household and nearly disappears once we control for this factor.
Keywords: H24; H31; J22; J65; 330; participation elasticities; labor supply; taxation; cross-country comparisons